Do Managerial Motives Influence Firm Risk Reduction Strategies? - May, Don O (Journal of Finance, 1995)
This article finds evidence consistent with the hypothesis that managers consider personal risk when making decisions that affect firm risk. The author finds that chief executive officers (CEOs) with more personal wealth vested in firm equity tend to diversify. CEOs who are specialists at the existing technology tend to buy similar technologies. When specialists have many years vested, they tend to diversify, however. Poor performance in the existing lines of business is associated with movements into new lines of business.